A short-term manual for webcam-based telemedicine treatment of Internet use disorders - Pape, Magdalena; Geisler, Birte Linny; Cornelsen, Lorraine; Bottel, Laura; te Wildt, Bert Theodor; Dreier, Michael; Herpertz, Stephan; Dieris-Hirche, Jan (Frontiers in Psychiatry, 2023)
In recent decades, the number of people who experience their internet use behavior as problematic has risen dramatically. In Germany, a representative study from 2013 estimated the prevalence of internet use disorder (IUD) to be about 1.0%, with higher rates among younger people. A 2020 meta-analysis shows a global weighted average prevalence of 7.02%. This indicates that developing effective IUD treatment programs is more critical than ever. Studies show that motivational interviewing (MI) techniques are widely used and effective in treating substance abuse and IUDs. In addition, an increasing number of online-based health interventions are being developed to provide a low-threshold treatment option. This article presents a short-term online-based treatment manual for IUDs that combines MI techniques with therapy tools from cognitive behavioral therapy (CBT) and acceptance and commitment therapy (ACT). The manual includes 12 webcam-based therapy sessions, each lasting 50 minutes. Each session is framed by a standardized beginning, conclusion, outlook, and flexible session content. In addition, the manual contains example sessions to illustrate the therapeutic intervention. Finally, we discuss the advantages and disadvantages of online-based therapy compared to analog treatment settings and provide recommendations for dealing with these challenges. By combining established therapeutic approaches with an online-based therapeutic setting based on flexibility and motivation, we aim to provide a low-threshold solution for treating IUDs.